The role of fluoride in anion–π interaction with naphthalene diimide. Issue 44 (14th May 2019) - Tam, Teck Lip Dexter; Xu, Jian Wei
Abstract : The role of fluoride in anion–π interaction with naphthalene diimide (NDI) is dependent on the solvent used. Abstract : The role of fluoride in anion–π interaction with naphthalene diimide (NDI) is dependent on the solvent used. Here we show that in polar aprotic solvents like THF which does not contain any acidic protons, fluoride generates hydroxide that complexes with NDI and it is this complex that reduces NDI to NDI˙ − .